Analysis of an Improved Hybrid Stem Design for Total Hip Replacement (THR) / Solehuddin Shuib ... [et al.] - Shuib, Solehuddin; Ismail, Nur Faiqa; Yahya, Muhd Azman; Ahmed Shokri, Amran (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper proposed an improvement in design and analysis of hybrid prosthesis in total hip replacement. A hip implant is a method for an artificial hip replacement which is made of a material that is different and is selected depending on the study in terms of strength. A hip implant is often focused on the damage to the hip joint. There are various factors which involve damage to the hip such as osteoarthritis, stress shielding, etc. Referring to the various types of total hip replacement products, several factors have been taken to differentiate between each type including the material, design and performance of the product. This project focuses on the stem of total hip replacement. By using computer aid design (CAD) software Solidworks 2013, the stem was redesigned with improvement and underwent the analysis using ANSYS 15.0 to analyses the behaviour which include the total deformation and equivalent (Von-Mises) stress.Higher stress shielding were found at the neck of the hip implant.The three major design types of the hip stems were compared in this study, and the design three (3) hip implant is the most stable among the others after being simulated using different activities.